2019
DOI: 10.1038/s41390-019-0284-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyunsaturated fatty acids on postnatal ileum development using the fat-1 transgenic mouse model

Abstract: Background Long-chain polyunsaturated fatty acids (LCPUFAs) play a critical role in neonatal health. We hypothesized that LCPUFAs play an essential role in priming postnatal gut development. We studied the effect of LCPUFAs on postnatal gut development using fat-1 transgenic mice, which are capable of converting n-6 to n-3 LCPUFAs, and wild-type (WT) C57BL/6 mice. Results Fat-1 mice, relative to WT mice, showed increased n-3 LCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…This study confirmed that fatty acid exposure and intestinal levels do impact postnatal intestinal development and that a balance between both n-3 and n-6 may be critical in this early developmental period. In the pre-weaning period, while an n-3 dominant pattern increased gene expression of cell differentiation markers (EphB2, Fzd5) and fatty acid metabolism (fatty acid binding protein 2 and 6), this n-3 dominant pattern also decreased villus height over time and reduced expression of markers that inform innate host defenses, such as a reduced number of acidic mucin filled goblet cells, reduced expression of tight-junction genes (claudin 3 and 7), and reduced gene expression of muc2, trefoil factor 3, toll like receptor 9, and cathelicidin antimicrobial peptide [52]. These data suggest that that LCPUFA changes reflective of those seen in neonatal intensive care units likely influence the trajectory of postnatal intestinal development.…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 93%
See 3 more Smart Citations
“…This study confirmed that fatty acid exposure and intestinal levels do impact postnatal intestinal development and that a balance between both n-3 and n-6 may be critical in this early developmental period. In the pre-weaning period, while an n-3 dominant pattern increased gene expression of cell differentiation markers (EphB2, Fzd5) and fatty acid metabolism (fatty acid binding protein 2 and 6), this n-3 dominant pattern also decreased villus height over time and reduced expression of markers that inform innate host defenses, such as a reduced number of acidic mucin filled goblet cells, reduced expression of tight-junction genes (claudin 3 and 7), and reduced gene expression of muc2, trefoil factor 3, toll like receptor 9, and cathelicidin antimicrobial peptide [52]. These data suggest that that LCPUFA changes reflective of those seen in neonatal intensive care units likely influence the trajectory of postnatal intestinal development.…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 93%
“…It is well-documented that in the early postnatal period of preterm infants, whole blood docosahexaenoic acid (DHA, C22:6n-3) and arachidonic acid (ARA, C20:4n-6) deficits and linoleic acid (LA, C18:2n-6) excesses occur within the first postnatal week [50]. Although these altered fatty acid profiles have been linked to the increased risk of developing bronchopulmonary dysplasia, retinopathy of prematurity, and late onset sepsis, the impact of these altered fatty acid profiles on intestinal development has just recently been described [50][51][52].…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intestinal permeability assay was performed as described previously (Singh et al, 2019). Briefly, mice were gavaged with FITC-dextran 4000 (FD-4) (Sigma-Aldrich) in PBS at a concentration of 600 mg/kg body weight.…”
Section: Measurement Of Intestinal Permeabilitymentioning
confidence: 99%